Judges' Consideration of Underage Marriage Dispensation Cases (Study of Decision Number 28/Pdt.P/2023/PA.Pwt) - Chikita Inezia Aletha Putri (Proceedings Series on Social Sciences & Humanities, 2023)
Marriage can be carried out if it meets the requirements in accordance with Marriage Law Number 1 of 1974 which states that marriage can be carried out if the man is 19 years old and the woman is 16 years old. But if in the event that a marriage will be carried out under this age, it is necessary to have a marriage dispensation from the authorized party, namely the court. A judge is asked for the discretion to decide on a marriage dispensation case either granting or refusing accompanied by strong considerations and reasons. An application for marriage dispensation is submitted by both male and female parents to the Religious Court for those who are Muslims in the area where they live. Judges as one of the pillars in the judicial process and law enforcement in the judicial area, namely receiving, examining, deciding and resolving cases that enter the court. This article is part of research that has been conducted in a normative juridical manner based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research and the problem to be studied is the consideration of judges in religious courts related to underage marriage dispensation cases. It is concluded that dispensation to enter into underage marriage is the absolute competence of the Religious Court for people who are Muslims. On the basis of the judge's consideration, the panel of judges will reject or grant the application in the form of a decision.